Avaliação do perfil de cardiopatias congênitas em filhos de mães diabéticas atendidos em hospital terciário no estado de São Paulo - Leite, Gabriela Silveira (Universidade Estadual Paulista (UNESP), 2025)
Introdução: As cardiopatias congênitas (CC) podem ser complicações fetais do diabetes mellitus materno (DM). Objetivo: Esse estudo teve como objetivo avaliar a prevalência de CC em filhos de mães diabéticas (FMDM), correlacionar os fenótipos cardíacos ao subtipo de DM materno e identificar fatores de risco associados. Metodologia: Desenvolveu-se um estudo de transversal retrospectivo com dados de 2013 a 2022. Foram selecionados 2.000 ecocardiogramas realizados em um hospital terciário de São Paulo, e analisados os prontuários apenas de FMDM, os quais foram divididos conforme o subtipo de DM: tipo 1, tipo 2 e gestacional. As variáveis estudadas incluíram sexo, idade materna, tabagismo, etilismo, malformações associadas e achados ecocardiográficos. Resultados: Foram identificados 264 FMDM; 124 apresentaram CC. As CC mais frequentes evidenciadas foram: miocardiopatia hipertrófica (31), persistência do canal arterial (25), comunicação interventricular (24) e interatrial. Tabagismo esteve presente em 12% das mães, com tendência a associação com CC. Todos os filhos de mães que consumiram álcool apresentaram defeitos cardíacos. Entre os que tinham CC, 29% tinham malformações associadas. Dentre os filhos de mães com DM tipo 1, 62,5% tinham alterações cardíacas. Conclusão: O perfil das CC em FMDM se assemelha ao da população geral, com destaque para a miocardiopatia hipertrófica, observada como predominante apenas nesse grupo.

Introduction: The development of congenital heart defects may be precipitated by maternal diabetes mellitus. Objective: Given the impact of maternal hyperglycemia on fetal cardiac abnormalities, this study aimed to determine the prevalence of congenital heart defects in the offspring of diabetic mothers, as well as to evaluate the correlation between the phenotypes of congenital heart disease and the subtype of maternal diabetes mellitus, and to identify other associated risk factors. Methodology: A retrospective cross-sectional study was conducted using data from 2013 to 2022. A total of 2,000 echocardiograms performed at a tertiary hospital in São Paulo were selected, and the electronic medical records of the children born to diabetic mothers were analyzed. These children were divided into three groups based on the subtype of maternal diabetes. The following variables were analyzed: sex, maternal age, maternal smoking and alcohol use, associated malformations, and echocardiogram results. Results: A total of 264 children of mothers with diabetes mellitus were identified, of whom 124 had congenital heart defects. The most common congenital heart defects observed were hypertrophic cardiomyopathy (31), patent ductus arteriosus (25), ventricular septal defect (24), and atrial septal defect. A total of 12% of the mothers were smokers, with a trend toward an association between smoking and congenital heart disease. All children of mothers who consumed alcohol had heart defects. 29% of the children with heart defects also had other malformations. 62.5% of the children born to mothers with type 1 diabetes had cardiac abnormalities. Conclusion: A similarity was observed between the profile of congenital heart defects in children of diabetic mothers and that of the general population.
Congenital Heart Diseases in Children of Diabetic Mothers Treated at a Tertiary Hospital in the State of São Paulo, Brazil
Keywords: Cardiopatia Congênita; Diabetes Mellitus; Filhos de mãe diabética; Malformações cardíacas